PRACTICAL TRAINING OF FUTURE BORDER GUARDS: FOREIGN COMMUNICATION AT BORDER CROSSING POINTS - Ірина БАСАРАБА; Ольга ЛЕМЕШКО (Bohdan Khmelnytskyi National Academy of the State Border Guard Service of Ukraine, 2022)
In connection with the increase of the level of terrorism, international crime, smuggling activities, and the military aggression of the russian federation against Ukraine, it became necessary to improve the system of countering these factors. In the documents regulating the professional training of personnel in the State Border Service of Ukraine (decrees of the President, resolutions of the Government of Ukraine, orders of the head of the State Border Guard Service of Ukraine, the Development Strategy of the State Border Guard Service of Ukraine), attention is focused on the need to train highly qualified officers capable of making effective decisions in the field of the state border of Ukraine protection. As a result of the theoretical analysis of the works of scientists, as well as the study of regulatory and legal documents on the organization of operational and service activities of the State Border Guard Service of Ukraine personnel, it was determined that the formation of professional readiness is an important prerequisite for the effective performance of professional tasks by officers. Graduates must have the appropriate level of competence to solve specific professional tasks. One of the main prerequisites for becoming a specialist in the border field is the acquisition of practical work experience, which involves applying theoretical knowledge in practice, mastering general and professional competencies, forming ideas about the specific activities of the future border guard officer. Practical training involves the creation of real conditions that project the future activities of a border guard officer. It should be noted that an integral part of the practical training of cadets is practice at the state border protection bodies, which is conducted to consolidate theoretical knowledge obtained at a certain stage of training in accordance with the direction, specialty, acquisition and improvement of professional skills and abilities. According to their official duties, border guards communicate with persons who cross the state border. It is necessary to adhere to the standards of communication, which are based on the observance of the rights and freedoms of citizens, courtesy, restraint, culture and brevity. Border guards must communicate foreign language within the scope of their official duties to conduct border representative meetings and conduct interviews with foreigners, so they must have foreign language communicative competence, which is one of the components of the professional competence of a border guard.